2023
DOI: 10.3390/electronics12183774
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Software Project Monitoring with Multidimensional Data Repository Mining

Łukasz Reszka,
Janusz Sosnowski,
Bartosz Dobrzyński

Abstract: Software project development and maintenance activities have been reported in various repositories. The data contained in these repositories have been widely used in various studies on specific problems, e.g., predicting bug appearance, allocating issues to developers, and identifying duplicated issues. Developed analysis schemes are usually based on simplified data models while issue report details are neglected. Confronting this problem requires a deep and wide-ranging exploration of software repository cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Both lists can be combined in one history list. Having analyzed a wide scope of ITS repositories [12], we found that depending upon the project, issue attributes and their values may differ partially or significantly. Usually, within the same project, they are stable; however, some fluctuation may appear in time, e.g., due to ITS system upgrades, project organization and development improvements, project actors' fluctuations, etc.…”
Section: Issue Tracking Spacementioning
confidence: 99%
See 4 more Smart Citations
“…Both lists can be combined in one history list. Having analyzed a wide scope of ITS repositories [12], we found that depending upon the project, issue attributes and their values may differ partially or significantly. Usually, within the same project, they are stable; however, some fluctuation may appear in time, e.g., due to ITS system upgrades, project organization and development improvements, project actors' fluctuations, etc.…”
Section: Issue Tracking Spacementioning
confidence: 99%
“…Depending upon the project, the number of issue attributes is in the range of a few dozen to more than 100. However, only some of them can be useful in the analysis [12]. The ITS records individual issue features to provide project actors with information on their processing.…”
Section: Issue Tracking Spacementioning
confidence: 99%
See 3 more Smart Citations